Logistics and Risk Assessment of Trekking Expeditions - Piotr KISIELEWSKI; Katarzyna BRZOZOWSKA (Communications of International Proceedings, 2024)
The aim of the paper is to assess the importance of logistics in organizing trekking expeditions by presenting and discussing tools supporting planning and control of implementation of individual phases of the expedition, such as the CPM and PERT operational methods or a Gantt chart, as well as the Just In Time logistic concepts that are also used at every phase of the expedition projects to improve the quality of expedition organization and optimize the costs. The paper presents the essence of trekking and its types with particular emphasis on mountain trekking, as well as the essence of logistics - its significance and scope which applies to organizing expeditions. Based on the authors' own experience and the collected literature, the stage of trekking planning are discussed, and the risk assessment and risk management method are formulated on the example of a trekking expedition in the selected sections of the Te Araroa trail in New Zealand.
Keywords: trekking expeditions; logistics; risk assessment